Impacts of the InovAgro II Project in Northern Mozambique - Ghebru, Hosaena; Smart, Jenny (2019)
Hoseana Ghebru and Jenny Smart WORKSHOP Market Systems Development Best Practices Dissemination Workshop Co-Organized by the CGIAR Research Program on Policies, Institutions, and Markets (PIM), The Swiss Agency for Development and Cooperation (SDC), and Development Alternatives Inc. (DAI) JUL 18, 2019 - 08:00 AM TO 03:15 PM CAT